Crystal structure of bis(dimethylammonium) hexaaquanickel(II) bis(sulfate) dihydrate - Held, Peter (Acta Crystallogr Sect E Struct Rep Online, 2014)
In the title salt, (C(2)H(8)N)(2)[Ni(H(2)O)(6))](SO(4))(2)·2H(2)O, the Ni(II) cation is located on a centre of inversion and exhibits a slightly distorted octahedral arrangement of water molecules. The Ni—O bond lengths in the complex [Ni(H(2)O)(6)](2+) cation show a distribution as in the related Tutton salt (NH(4))(2)[Ni(H(2)O)(6)](SO(4))(2), but are longer in average [2.056 (13) versus 2.037 (12) Å]. The noncoordinating water molecules and dimethylammonium cations connect the sulfate and [Ni(H(2)O)(6)](2+) octahedra via O—H⋯O and N—H⋯O hydrogen bonds from weak up to medium strength into a three-dimensional framework whereby the complex metal cations and sulfate anions are arranged in sheets parallel (001).